2004
DOI: 10.1038/modpathol.3800100
|View full text |Cite
|
Sign up to set email alerts
|

Application of SELDI-TOF mass spectrometry for the identification of differentially expressed proteins in transformed follicular lymphoma

Abstract: Completion of the human genome project has focused scientific attention on the development of methods that permit rapid characterization of proteins that are encoded by the genome. Recent improvements in twodimensional separation techniques in combination with protein identification software/databases and mass spectrometry (MS) now permit rapid comprehensive large-scale analysis of individual proteins within complex protein mixtures. We have performed pairwise comparisons of low-grade and transformed follicula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Another proteomic based study identified proteins of different cellular fractions from Hodgkin lymphoma-derived cell lines as well as secreted proteins extracted from serum-free culture media (Wallentine et al 2007). Apart from HL there are few proteomic studies on different Non-Hodgkin lymphomas such as anaplastic large cell lymphoma (Crockett et al 2005), mantle-cell lymphoma (Ghobrial et al 2005), follicular lymphoma as well as cell lines from different lymphoid neoplasms (Fujii et al 2005;Lin et al 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Another proteomic based study identified proteins of different cellular fractions from Hodgkin lymphoma-derived cell lines as well as secreted proteins extracted from serum-free culture media (Wallentine et al 2007). Apart from HL there are few proteomic studies on different Non-Hodgkin lymphomas such as anaplastic large cell lymphoma (Crockett et al 2005), mantle-cell lymphoma (Ghobrial et al 2005), follicular lymphoma as well as cell lines from different lymphoid neoplasms (Fujii et al 2005;Lin et al 2004).…”
Section: Discussionmentioning
confidence: 98%
“…It is now clear that SELDI profiling of the proteome can successfully detect anonymous proteins that are produced at higher (or lower) concentrations in the tissues or fluids of cancer patients than in healthy individuals (1)(2)(3). There is also preliminary evidence that we may be able to discover patterns that can reliably distinguish cancer patients from healthy individuals (4 -7 ).…”
mentioning
confidence: 89%
“…These mass spectral patterns can be used to differentiate patient samples from one another, such as from normal versus diseased. Although, this technology was initially used specifically to determine the mass-to-charge ratio of proteins within a sample, more recently SELDI-TOF instruments coupled to tandem mass spectrometers have been developed to enable protein identification and quantitation [58][59][60].…”
Section: Seldi-tofmentioning
confidence: 99%